2020
DOI: 10.21203/rs.3.rs-23519/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Diameter of Superior Rectal Vein – CT Predictor of KRAS mutation in Rectal Carcinoma

Abstract: Background The purpose of this study was to investigate the feasibility of CT parameters to predict the presence of KRAS mutation in rectal cancer patients. The relationship between KRAS mutation and pathological findings was evaluated simultaneously.Methods 89 patients (29 females, 60 males, age 27–90, mean 59.7 ± 12 years) with pathologically proven rectal cancer were enrolled. KRAS mutation test was completed following surgery. Parameters evaluated on CT included the diameter of superior rectal vein (SRV) a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…( 6) Some studies have found that the dSRV can not only be used as a predictor of lymphatic vascular invasion and lymph node metastasis of rectal cancer (6, 7) but is also valuable in determining whether liver lesions are metastatic lesions and predicting KRAS mutations in rectal cancer. (8,9) Although it has been reported that the dSRV in patients with metastasis is wider than that in patients without metastasis, (6) some studies have reported different results, and there is no signi cant difference in the dSRV between patients with metastasis and those without metastasis. (7) At present, research on the role of the superior rectal vein in rectal cancer is still controversial, and the related studies are few.…”
Section: Introductionmentioning
confidence: 99%
“…( 6) Some studies have found that the dSRV can not only be used as a predictor of lymphatic vascular invasion and lymph node metastasis of rectal cancer (6, 7) but is also valuable in determining whether liver lesions are metastatic lesions and predicting KRAS mutations in rectal cancer. (8,9) Although it has been reported that the dSRV in patients with metastasis is wider than that in patients without metastasis, (6) some studies have reported different results, and there is no signi cant difference in the dSRV between patients with metastasis and those without metastasis. (7) At present, research on the role of the superior rectal vein in rectal cancer is still controversial, and the related studies are few.…”
Section: Introductionmentioning
confidence: 99%